PEMANFAATAN LAMPU PENERANGAN JALAN UMUM HEMAT ENERGI BERBASIS PANEL SURYA MENGGUNAKAN KONTROL PID DI DUSUN TUMPANGREJO,DESA NGENEP, KARANGPLOSO, KAB. MALANG - Bambang Minto Basuki; , Abdul Muta’ali; Doni Prasetyo (FIP UNIRA MALANG, 2026)
ABSTRACT The quality of nighttime lighting in Tumpangrejo Hamlet, Ngenep Village was limited, affecting both residents’ safety and their daily activities. These conditions emphasized the need for a community service program that could help address local challenges. This program implemented solar-powered street lighting (PJU) equipped with PID control as an efficient and sustainable renewable energy solution. The implementation methods included site surveys, mapping of installation points, measurement of light intensity, installation of the solar panel system, and community outreach. The results indicated a significant improvement in nighttime illumination levels, increased energy efficiency, and enhanced residents’ sense of safety. Moreover, the community gained a better understanding of basic maintenance for solar energy systems. These outcomes demonstrate that solar-powered street lighting is a viable option to support village energy independence